Spud - Van de Ruit, John. (New York : Razorbill, 2007)
In 1990, thirteen-year-old John "Spud" Milton, a prepubescent choirboy, keeps a diary of his first year at an elite, boys-only boarding school in South Africa, as he deals with bizarre housemates, wild crushes, embarrassingly dysfunctional parents, and much more.
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Choirboys -- Fiction; Family life -- South Africa -- Fiction; Diaries -- Fiction; Humorous stories; South Africa -- Fiction